Study of Histopathological Patterns in Breast Lumps - Shalini Kashyap; Sachin Chauhan (Asian Journal of Medical Research, 2020)
Background: Breast lesions in females are heterogeneous diseases that consist of several distinct entities with remarkably different characteristic features. The present study was conducted to assess histopathological findings of excision biopsies of breast lesions.Subjects and Methods:The present study was conducted on 150 cases of lumpectomy breast specimens received in the department of histopathology. The histopathological diagnosis made after routine processing and hematoxlin and eosin staining.Results:The most common age group of presentation was 30 to 50 years having well defined breast mass lesion. The difference was significant (P< 0.05). Among 150 breast specimens, 145 found to be benign and 05 malignant. In benign, common lesions were fibroadenoma in 64, fibroadenosis in 30, Acute Suppurativeinflammatory lesion (Abscess) in 20, fibrocystic disease (FCD) in 22, duct papilloma in 05 and benign phyllodes in 04 cases. In malignant, 04 cases were infiltrative ductal cell carcinoma NOS (Not otherwise specified) and 01 carcinoma in situ. The difference was significant (P< 0.05).Conclusion: Authors found that most common benign breast lesions were fibroadenoma (44.1%) and fibroadenosis (20.6%) followed by acute suppurative inflammatory (Abscess) and  FCD.